The Hitler years, Volume 1 triumph 1933-1939 - McDonough, Frank 1957- (Head of Zeus, 2019)
A new narrative of the rise and catastrophic fall of the Nazi regime: a twelve-year descent into barbarism, genocide and aggressive war that cost over 50 million lives.